1996
DOI: 10.1038/bjc.1996.291
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of steroid receptors after long-term follow-up of 2257 operable breast cancers

Abstract: S_inary The prognostic value of oestrogen receptor (ER) and progesterone receptor (PR) was estimated through a multicentric study of 2257 operable breast cancer patients followed up for a median of 8.5 years. None of the patients had received adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 15 publications
11
65
1
2
Order By: Relevance
“…However, the association found in our study is time-dependent. Nonetheless, in some breast cancer studies, several prognosis factors have been identified with a time-dependent effect that decreases during the follow-up [24][25][26]. On the contrary, we found that CBC hazard is increased during the long term follow-up among overweight and obese patients.…”
Section: Discussioncontrasting
confidence: 61%
“…However, the association found in our study is time-dependent. Nonetheless, in some breast cancer studies, several prognosis factors have been identified with a time-dependent effect that decreases during the follow-up [24][25][26]. On the contrary, we found that CBC hazard is increased during the long term follow-up among overweight and obese patients.…”
Section: Discussioncontrasting
confidence: 61%
“…13 There has been strong evidence of a nonproportional effect of ER as indicated by the loss of its predictive value over long periods of patient follow-up. 28 For this study, tests of proportionality of PR on disease-free and overall survival over the follow-up period were performed using hypothesis tests of PR as a time-dependent variable in the Cox model, as well as examining plots of the beta coefficients of PR from the Cox model vs follow-up time. 29 For this study population, evidence of nonproportionality of PR was not detected, and Cox models were therefore developed without adjustment for PR as a time-dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…A weakness in our study is the median FU period which consisted of 3.5 years only and which allows us only short-term DFI interpretations. Others have referred to ER and PR as only being short-term prognostic factors whereas little data are available on HER-2 as a prognostic factor beyond five years of FU [6,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of these predictive biomarkers can be summarized as follows. Women with an ER-positive tumor have a better prognosis than those with an ER-negative tumor, although this is not true for very young women and not after approximately eight years of follow-up (FU) when survival curves of ER-positive and ER-negative cases cross [5][6][7]. The combination of ER with PR further refines the short-term prognostic value of ER.…”
Section: Introductionmentioning
confidence: 99%